Development of Mathematic Learning Set Based On Pedagogical Content Knowledge to Improve Mathematics Problem Solving Ability - Ibut Priono Leksono; Sri Rahmawati Fitriatien (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
This research use development research wich aim to product mathematic learning that include implementation plans and woksheets based on pedagogical content knowledge in order to improve mathematical problem solving ability. The development model that used in this research uses four stages starting with define, then continue with design stage, next the develop stage, and the last stage is disseminate stage, or better known as 4D model. The mathematical problems that used in this research include linear programming problems that are solved with the integer programming method. The results of validation for the result of learning tools show that the pedagogical content knowledge with 4D method are suitable to used with very good categories. Meanwhile, the trial results show that the pedagogical content knowledge learning tools produced are practical and effective. This is able to support an achievement of research object that is able to improve the ability of students to solve math problems for linear programe case by using integer programming method. Keywords: pedagogical content knowledge, problem solving, math problem, integer programming.